Knowledge, Beliefs, Behaviors, and Social Norms Related to Use of Alternative Tobacco Products Among Undergraduate and Graduate Nursing Students in an Urban U.S. University Setting. Issue 2 (4th February 2016) - VanDevanter, Nancy; Zhou, Sherry; Katigbak, Carina; Naegle, Madeline; Sherman, Scott; Weitzman, Michael
Abstract: Purpose: The purpose of the study was to assess nursing students' knowledge, beliefs, behaviors, and social norms regarding use of alternative tobacco products (ATPs). Design and Methods: This anonymous online survey was conducted with all students enrolled in a college of nursing. The survey utilized measures from several national tobacco studies to assess knowledge and beliefs about ATPs (hookahs, cigars or cigarillos, bidis, kreteks, smokeless tobacco, electronic cigarettes) compared to cigarettes, health effects of ATPs, personal use of ATPs, and social norms. Data were analyzed in SPSS 22.0 (SPSS Inc., Chicago, IL, USA). Descriptive statistics and frequencies were performed for basic sociodemographic data. Paired samples t tests were performed to determine differences for scaled measures. Findings: Nursing students demonstrated very low levels of knowledge about ATPs and their health consequences, despite high rates of ATP personal use. About 76% of participants reported use of one or more ATPs once or more in their lifetimes. A greater proportion of students had used hookahs or waterpipes (39.6%) compared to cigarettes (32.7%). Conclusions: Nurses' lack of knowledge about the emerging use and health threats associated with ATPs may undermine their ability to provide appropriate tobacco cessation counseling. Research is needed to identify gaps in nurses' education regarding tobacco cessation counseling and to develop new counseling approaches specific to use of ATPs. Clinical Relevance: Nurses play critical roles in counseling their patients for tobacco cessation. Further research and education about the risks presented by ATPs are critical to reducing excess tobacco‐related mortality.